2013
DOI: 10.1007/s12298-013-0165-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of calcium in improving photosynthesis and related physiological and biochemical attributes of spring wheat subjected to simulated acid rain

Abstract: The response of photosynthesis parameters, catalase, superoxide dismutase and peroxidase activity, malondialdehyde, proline, chlorophyll, yield and yield components to foliar application of calcium and simulated acid rain in wheat were investigated. Foliar treatment of calcium led to significant increases in the photosynthesis rate, transpiration rate, stomatal conductance, proline, chlorophyll, yield and yield components in plants subjected to acid rain. Antioxidant enzyme activity and lipid peroxidation in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 45 publications
4
21
0
Order By: Relevance
“…Among these defensive enzymes, SOD functions as the frontline protector against superoxide radicals which are further scavenged either by catalases (CATs) or APX through ascorbate-glutathione pathway, resulting in its removal which avoids the subsequent more toxic radical formation (Ahmad et al 2010, Bose et al 2013. Our results of improved antioxidant metabolism due to Ca supplementation corroborate the findings of Arshi et al (2010) and Dolatabadian et al (2013). Exogenous application of Ca to Festuca arundinacea and Poa pratensis resulted in mitigation of heat stress by improving SOD activity (Jiang and Huang 2001).…”
Section: Discussionsupporting
confidence: 91%
“…Among these defensive enzymes, SOD functions as the frontline protector against superoxide radicals which are further scavenged either by catalases (CATs) or APX through ascorbate-glutathione pathway, resulting in its removal which avoids the subsequent more toxic radical formation (Ahmad et al 2010, Bose et al 2013. Our results of improved antioxidant metabolism due to Ca supplementation corroborate the findings of Arshi et al (2010) and Dolatabadian et al (2013). Exogenous application of Ca to Festuca arundinacea and Poa pratensis resulted in mitigation of heat stress by improving SOD activity (Jiang and Huang 2001).…”
Section: Discussionsupporting
confidence: 91%
“…It has been reported that chlorophyll deterioration is one of the first symptoms of calcium deficit; therefore, an increase in cellular calcium will lead to an increase in chlorophyll content of plants (Dolatabadian et al . ). Irfan et al .…”
Section: Resultsmentioning
confidence: 97%
“…Reduction of SOD activity after AR treatment was also observed in other plants and presented in several works (He et al 2011;Tong et al 2005). On the other hand, there are some articles in which increases in SOD activity were observed as the effects of AR treatment (Dolatabadian et al 2013). Chen et al (2013) reported much higher constitutive SOD activity in Schima superb, a plant species tolerant to AR, than in AR-sensitive plants and this activity did not change considerably after appearance of AR stress factor.…”
Section: Discussionmentioning
confidence: 99%